2012
DOI: 10.1161/hypertensionaha.112.193805
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase Gene Targeting to Adipocytes Attenuates Adiposity and Vascular Dysfunction in Mice Fed a High-Fat Diet

Abstract: We examined the hypothesis that adipocyte dysfunction in mice fed a high fat (HF) diet can be prevented by lentiviral-mediated and adipocyte specific-targeting delivery of the human heme oxygenase-1 (aP2-HO-1). A bolus intracardial injection of aP2-HO-1 resulted in expression of human HO-1 for up to 9.5 months. Transduction of aP2-HO-1 increased human HO-1 expression in fat tissues without affecting murine HO-1. In mice fed a HF diet, aP2-HO-1 transduction attenuated the increases in body weight, blood glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(123 citation statements)
references
References 54 publications
(76 reference statements)
10
112
1
Order By: Relevance
“…A recent study also showed that MC4R-deficient obese mice treated with long-term (4-23 weeks of age) CoPP administration, exhibited increased oxygen consumption, and CO2 and heat production [224]. Increased adiponectin has also been reported and has been proposed to underpin these beneficial effects [209,[225][226][227][228]. Studies have also shown that the above benefits can be reversed by SnMP treatment [210,217].…”
Section: Ho-1 and Obesitymentioning
confidence: 95%
See 4 more Smart Citations
“…A recent study also showed that MC4R-deficient obese mice treated with long-term (4-23 weeks of age) CoPP administration, exhibited increased oxygen consumption, and CO2 and heat production [224]. Increased adiponectin has also been reported and has been proposed to underpin these beneficial effects [209,[225][226][227][228]. Studies have also shown that the above benefits can be reversed by SnMP treatment [210,217].…”
Section: Ho-1 and Obesitymentioning
confidence: 95%
“…HO-1 induction remodels adipocytes, resulting in hyperplasia instead of hypertrophy. These adipocytes increase the production of AMPK, PPARγ, and adiponectin, at the same time decreasing the production of inflammatory markers and cytokines [209,210,215,243].…”
Section: Ho-1 and Adipocytesmentioning
confidence: 99%
See 3 more Smart Citations